2022
DOI: 10.1111/mcn.13321
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition matters: Association of stunting and underweight with early childhood development indicators in Nepal

Abstract: Malnutrition is a threat to optimal child development, with its occurrence during foetal and infancy stages associated with poor cognitive, motor and socio-emotional skills. However, information on the effects of various types of malnutrition on early childhood development (ECD) is limited in Nepal. To assess the association of stunting, wasting and underweight (three prominent forms of malnutrition) with the four domains of the ECD index (literacy-numeracy, physical, social-emotional and learning development)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Our study identified being stunted, along with household SES and mother's education, as a significant risk factor for SDD among children, which is also supported by previous studies 7,21,[49][50][51][52] . A recent study mentioned that around 10% of the prevalence of suspected delay in cognitive domain could be eliminated by eliminating stunting in LMICs, highlighting the need for reducing stunting prevalence in relation to child development 53 .…”
Section: Socioeconomic Inequalitysupporting
confidence: 90%
See 1 more Smart Citation
“…Our study identified being stunted, along with household SES and mother's education, as a significant risk factor for SDD among children, which is also supported by previous studies 7,21,[49][50][51][52] . A recent study mentioned that around 10% of the prevalence of suspected delay in cognitive domain could be eliminated by eliminating stunting in LMICs, highlighting the need for reducing stunting prevalence in relation to child development 53 .…”
Section: Socioeconomic Inequalitysupporting
confidence: 90%
“…In addition, a recent study reported delayed gross motor development among girls aged 3 years who underwent delayed cord clamping 20 . Yet, to our knowledge, studies identifying potential risk factors of SDD among younger Nepalese children using wide range of covariates are limited [18][19][20][21] .…”
mentioning
confidence: 99%
“…Socioeconomic factors, such as family income and access to resources, in uence the availability of educational and health opportunities; the number of children ever born is also found to be associated with ECD [3,7]. Moreover, the linkage between child malnutrition and ECD is well-established, with malnourished children usually reported to have suboptimal ECD or vice versa [10][11][12][13]. Furthermore, the broader community context, including cultural norms and societal support systems, contributes signi cantly to a child's developmental trajectory [7].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is the cause of 45% of deaths in children under 5 years of age worldwide [5]. Not only in Indonesia, stunting or malnutrition is a problem that has been widely studied around the world, such as in research in Nepal [6], Serbia [7], Pakistan [8], and other countries.. The quality of the population in the future is influenced by the quality of the current growth of the baby.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition plays an important role in the development of children aged 0-59 months [8]. Malnutrition or mistakes in choosing food menus for babies cause malnutrition or stunting problems [6]. In the short term, this can cause brain, intelligence, physical growth, and metabolism disorders in children.…”
Section: Introductionmentioning
confidence: 99%